IoT-Based Smart Dorm Key System Using Voice Password and Fingerprint Authentication for Dormitory Access Control - DTM Faiq Zariaqwila; Rita Purnamasari; Efri Suhartono (Forum Kerjasama Pendidikan Tinggi (FKPT), 2026)
The Internet of Things (IoT) has become an important technology in the development of modern access control systems. This study presents the design and implementation of an IoT-based Smart Dorm Key system employing a two-factor authentication mechanism using voice password verification and fingerprint authentication to improve dormitory access security. The proposed system is designed for Telkom University dormitories and enables real-time access control, monitoring, and access log synchronization through internet connectivity. The system utilizes an ESP32 microcontroller as the main controller integrated with an AS608 fingerprint sensor, solenoid door lock, no-touch sensor, LCD display, and buzzer to support authentication and door operation. Voice password verification is performed through a mobile application as the first authentication layer before fingerprint verification is conducted as the second layer. Experimental results show that the fingerprint sensor achieved 100% accuracy under normal conditions, while its performance decreased under wet and dirty finger conditions with accuracy values of 8% and 11%, respectively. The no-touch sensor operated reliably with a maximum detection distance of 10.5 cm. The results indicate that the proposed system is capable of implementing layered authentication and real-time monitoring, although further improvement is required to enhance performance under non-ideal conditions.